(untitled) (Communication & Society, 2004)
Radio Broadcasting genres theory used to focus on adaptation of printed media news writing, not pointing to such specific items as: voice of the discourse, oral communication properties, short life of the messages and non linguistic elements, all of which do not found properly approach under that theory. This article aims to set up the basement for a Radio Broadcasting genres theory gathering the theroretical developments reached in Spain. We describe and evaluate the theroretical corpus in order to propose guideliness and variables to consider in order to develop this new theory.